La bayadère - Minkus, L. 1826-1917 (Bel Air Media -- The State Academic Bolshoi Theatre of Russia, 2013)
For the very first time in its history, medici.tv associates with one of the world's most prestigious companies, the Ballet of the State Academic Bolshoi Theatre of Russia, for a new scenic version of Marius Petipa's La Bayadère, revised by Yuri Grigorovich. It is one of the greatest ballets of the repertoire. Its choreography gathers a huge amount of dancers, including at least five highly virtuoso soloists. Premiered in 1877 at the State Academic Bolshoi Theatre of Russia, La Bayadère was choreographed by Marius Petipa on a score by Leon Minkus. It was revised a few times -- by Petipa himself, and then by other choreographers. A milestone of the Russian repertoire, the ballet stayed unknown in Western countries --
Keywords: Ballets; Dancers; Man-woman relationships; Temples; Temples -- India -- Golconda -- Drama; Dancers -- India -- Golconda -- Drama; Man-woman relationships -- India -- Golconda -- Drama; India / Golconda; Drama; Internet videos